China's Debt Trap in Indonesia: A Case Study of the Jakarta-Bandung High-Speed Rail Project - Nabiilah, Rifia Azka; Deasy Silvya Sari (Ilomata International Journal of Social Science, 2024)
Thanks to the Belt and Road Initiative, the rise of China has brought forth new sets of opportunities and challenges for Southeast Asia. Indonesia has become one of Southeast Asia countries that has close economic relations with China. The Indonesia-China High Speed Rail project, which connects Jakarta-Bandung with a 142 km long line, can be seen as one of the biggest projects between Indonesia and China. However, the project faces an overrun of around USD 2 billion. This paper aims to analyze the worst possibility that Indonesia will face, namely China's Debt Trap. This paper uses the literature study method. The results show that Indonesia has the potential to be caught in China's debt-trap if there are no comprehensive economic recovery efforts without relying on foreign loans. State income from loans and debts will only lead Indonesia under the influence of the lender country. This paper suggests that Indonesia needs to reconsider its decision to use APBN funds for a new capital project, namely Nusantara. This can make Indonesia trapped in a debt-trap due to excessive reduction in state assets.